2014
DOI: 10.5194/acp-14-9295-2014
|View full text |Cite
|
Sign up to set email alerts
|

On the wintertime low bias of Northern Hemisphere carbon monoxide found in global model simulations

Abstract: Abstract. Despite the developments in the global modelling of chemistry and of the parameterization of the physical processes, carbon monoxide (CO) concentrations remain underestimated during Northern Hemisphere (NH) winter by most state-of-the-art chemistry transport models. The consequential model bias can in principle originate from either an underestimation of CO sources or an overestimation of its sinks. We address both the role of surface sources and sinks with a series of MOZART (Model for Ozone And Rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(164 citation statements)
references
References 92 publications
13
129
1
Order By: Relevance
“…22a (Fortems-Cheiney et al, 2011) and Fig. 22b (Tohjima et al, 2014), more particularly at midlatitudes of the Northern Hemisphere in winter (Kopacz et al, 2010;Stein et al, 2014). However, an analysis of satellite and aircraft observations has also shown that emissions inventories in North America might provide overestimated values (Miller et al, 2008).…”
Section: Evaluation and Optimisation Of Emissions Using Inverse Modelmentioning
confidence: 99%
“…22a (Fortems-Cheiney et al, 2011) and Fig. 22b (Tohjima et al, 2014), more particularly at midlatitudes of the Northern Hemisphere in winter (Kopacz et al, 2010;Stein et al, 2014). However, an analysis of satellite and aircraft observations has also shown that emissions inventories in North America might provide overestimated values (Miller et al, 2008).…”
Section: Evaluation and Optimisation Of Emissions Using Inverse Modelmentioning
confidence: 99%
“…The estimated winter emissions of Kopacz et al (2010) are about 50 % larger than the summer emissions. Kopacz et al (2010) and Stein et al (2014) attributed the higher wintertime emissions in the Northern Hemisphere to vehicular emissions, which are not account for in the a priori emission inventory.…”
Section: Co Source Estimates For June 2004-may 2005mentioning
confidence: 99%
“…B00 and E04; see also Stein et al, 2014, and references therein). Stein et al (2014) show that a more detailed representation of the strength and seasonality of CO dry deposition fluxes and traffic emissions in Europe and North America leads to more adequately reproduced NH CO mixing ratios. It is noteworthy that their hypothesis that the missing traffic CO is due to emission inventories not accounting for cold-start engine conditions should be verifiable through 18 O / 16 O ratio of emitted CO: the latter (but unfortunately not 13 C / 12 C ratio) differ substantially between the BB and FF sources (see Kato et al, 1999a, also Sect.…”
Section: Discussionmentioning
confidence: 99%
“…2), as well as in other employed models/inventories (e.g. B00 and E04; see also Stein et al, 2014, and references therein). Stein et al (2014) show that a more detailed representation of the strength and seasonality of CO dry deposition fluxes and traffic emissions in Europe and North America leads to more adequately reproduced NH CO mixing ratios.…”
Section: Discussionmentioning
confidence: 99%